2020
DOI: 10.1182/bloodadvances.2019000992
|View full text |Cite
|
Sign up to set email alerts
|

Low VWF levels in children and lack of association with bleeding in children undergoing tonsillectomy

Abstract: Key Points In children undergoing tonsillectomy, low VWF levels did not predict surgical bleeding in the absence of major bleeding history. Children have lower VWF levels than adults and these lower levels do not appear to be associated with bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…However, the number of patients in the low VWF and disease categories, especially among those who experienced bleeding, was very small and may have influenced our ability to capture any differences. Gill et al 27 also noted the transient nature of low VWF values, especially in children. Interestingly, we found that nearly one-third of patients who had a known BT and were categorized as low VWF in our study had a subsequent normal VWD panel result prior to their procedure, did not receive treatment based on clinician or family preference, and did not have bleeding postoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…However, the number of patients in the low VWF and disease categories, especially among those who experienced bleeding, was very small and may have influenced our ability to capture any differences. Gill et al 27 also noted the transient nature of low VWF values, especially in children. Interestingly, we found that nearly one-third of patients who had a known BT and were categorized as low VWF in our study had a subsequent normal VWD panel result prior to their procedure, did not receive treatment based on clinician or family preference, and did not have bleeding postoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…15 Studies have demonstrated that many patients with reduced VWF levels in the 30 to 50 IU/dL range do not have a significant bleeding phenotype. 61 Consequently, a critical first step in diagnosis is to objectively assess bleeding using a validated BAT. The 2 scores most widely used in this context are the ISTH and condensed MCMDM-1 VWD BATs.…”
Section: Abo Blood Group and Low Vwfmentioning
confidence: 99%
“…Thus, although reduced VWF levels in the 30 to 50 IU/dL range may constitute a risk factor for bleeding, they may not be sufficient to cause a bleeding phenotype in the absence of other hemostatic factors. 14,61,62 However, it also seems likely that a significant cohort of patients with low VWF and bleeding complications (particularly women with HMB) is not being diagnosed. 18 Given the significant associated morbidity, it is imperative that awareness among the general population and health care professionals is actively promoted.…”
Section: Abo Blood Group and Low Vwfmentioning
confidence: 99%
See 1 more Smart Citation
“…Low von Willebrand factor (VWF) is an intermediate reduction in plasma VWF levels (30‐49%) and is generally considered a risk factor for bleeding but not a bleeding disorder 1‐3 . Low VWF poses a number of diagnostic and therapeutic challenges for both patients and providers since individuals report heterogeneous bleeding phenotypes.…”
Section: Introductionmentioning
confidence: 99%